LINC01857 as an oncogene regulates CREB1 activation by interacting with CREBBP in breast cancer. Issue 8 (9th January 2019) - Xiong, Youyi; Gu, Yuanting; Wang, Fang; Li, Lin; Zhu, Mingzhi; Wang, Nan; Mi, Hailong; Qiu, Xinguang
Abstract: Breast cancer is a one of the most malignant threats among women worldwide. However, the mechanism underlying breast cancer development remains unclear. Long noncoding RNAs (lncRNAs) have been reported to participate in breast cancer. Whether lncRNA LINC01857 is involved in breast cancer requires investigation. In this study, we found that LINC01857 was highly expressed in breast cancer tissues and cells ( p < 0.05). High LINC01857 expression predicted poor prognosis in breast cancer patients. Functionally, LINC01857 silencing impaired proliferation and enhanced apoptosis of breast cancer cells ( p < 0.05). Decreased LINC01857 inhibited breast cancer cells migration and invasion ability ( p < 0.05). In terms of mechanism, LINC01857 promoted H3K27Ac deposition on CREB1 promoter and initiated its transcription by recruiting CREBBP. Overexpression of CREB1 reversed the biological behavior of breast cancer cells induced by LINC01857 silencing ( p < 0.05). Taken together, our findings demonstrated that LINC01857 promoted breast cancer development by promoting H3K27Ac and CREB1 transcription via enhancing CREBBP enrichment in the CREB1 promoter region. Abstract : LINC01857 as an oncogene regulates CREB1 activation by interacting with CREBBP in breast cancer.